How COVID-19 Affects Agricultural Food Sales: Based on the Perspective of China’s Agricultural Listed Companies’ Financial Statements - Jianxiong Chen; Chung-Cheng Yang (Agriculture, 2021)
Agricultural food is generally regarded as the basis of “national security” by most countries. Through marketing strategies, promoting the sales of agri-food products in the context of a pandemic is of great significance to national food security and economic growth. The purpose of our study is to understand how the COVID-19 crisis affects the sales of agri-food products as well as the organizational and management changes it brings. By understanding those points above, we can address the problem and policy challenges to better promote the recovery of the agri-food sector from the effects caused by COVID-19. The demand is today overwhelmingly urgent. Based on the data of China’s agricultural-listed companies from 2015 to 2020, this study adopted the perspective of financial statements and conducted empirical analysis through the translog revenue function, and the results showed that the COVID-19 pandemic has reduced the sales of agri-food products, and the sales of agri-food products by large agricultural companies have fallen more than those of small- and medium-sized ones. Based on the results of the study, the government can consider the policy of providing financial support and temporary subsidies to agri-food enterprises during the pandemic, while agri-food enterprises actively practice digital marketing to reduce the adverse impact of COVID-19 on agri-food sales.